2017
DOI: 10.1111/jgs.15012
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta‐Analysis of The Effect of Low Vitamin D on Cognition

Abstract: Observational evidence demonstrates low vitamin D is related to poorer cognition; however, interventional studies are yet to show a clear benefit from vitamin D supplementation. From the evidence to date, there is likely a therapeutic age window relevant to the development of disease and therefore vitamin D therapy. Longitudinal lifespan studies are necessary to depict the optimal timing and duration in which repletion of vitamin D may protect against cognitive decline and dementia in aging, to better inform t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
128
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(140 citation statements)
references
References 57 publications
6
128
1
1
Order By: Relevance
“…In the present study, we found an association between vitamin D levels of ≤18 ng mL À1 and a higher prevalence of cognitive decline. Similarly, a systematic review and meta-analysis developed by Goodwill and Szoeke (32) that included 26 observational studies found an association between low vitamin D levels (ranging from <25 to <50 nmol L À1 ) and worse cognitive performance. In their meta-analysis, Shen and Ji also found that subjects with vitamin D deficiency [25(OH)D levels <50 nmol L À1 ] were at increased risk of developing Alzheimer's disease compared to those with 25(OH)D levels of ≥50 nmol L À1 (33) .…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, we found an association between vitamin D levels of ≤18 ng mL À1 and a higher prevalence of cognitive decline. Similarly, a systematic review and meta-analysis developed by Goodwill and Szoeke (32) that included 26 observational studies found an association between low vitamin D levels (ranging from <25 to <50 nmol L À1 ) and worse cognitive performance. In their meta-analysis, Shen and Ji also found that subjects with vitamin D deficiency [25(OH)D levels <50 nmol L À1 ] were at increased risk of developing Alzheimer's disease compared to those with 25(OH)D levels of ≥50 nmol L À1 (33) .…”
Section: Discussionmentioning
confidence: 97%
“…Regarding domain‐specific cognitive abilities, mental speed and attention (summary OR = 1.23, P = .004) and visuospatial abilities (summary OR = 1.32, P = .03) had stronger associations with vitamin D than memory ( P = .19). Finally, vitamin D supplementation had no significant effect on cognition (standard mean difference = 0.21, 95% CI = −0.05–0.46) …”
mentioning
confidence: 91%
“…This issue of the Journal of the American Geriatrics Society contains an elegant systematic review and metaanalysis by Goodwill and Szoeke aimed at quantitatively assessing the effect of low vitamin D or vitamin D supplementation on cognition in midlife and older adults without a diagnosis of dementia . Twenty‐six observational (12 cross‐sectional, 14 longitudinal) and three interventional studies were included in the metaanalysis (n = 19–9,556).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mini-mental state examination (MMSE) has been the most commonly administered scale to assess the global cognitive functioning (Goodwill & Szoeke, 2017). However, the mini-mental state examination (MMSE) has been the most commonly administered scale to assess the global cognitive functioning (Goodwill & Szoeke, 2017).…”
mentioning
confidence: 99%